The Alternative Renewable Energy and their Developing Perspectives in Albania - Sefa, Stela; Gjini, Anjeza (Richtmann Publishing, 2012)
The present study analyzes the necessity of alternative energy sources for Albania, as a developing country, and theirimpact on the economy. If Albanian economy will directly depending on the use of hydro energy, it simply will not have enoughenergy capacity for its population. Renewable energy sources have the potential to make a large contribution to Albaniaâ€™ssustainable and independent energy future. Renewable energy production requires large investments, which increases theproduction cost of energy. Nevertheless â€œhigh costâ€ investment should not impede the development of Albania in this sectorsince the benefit is much greater than the â€œcostâ€. Any kind of investment in renewable energy such as a solar energy, windenergy, biomass, geothermal energy etc is profitable. Many other countries of Europe have started years ago investment inrenewable. Albaniaâ€™s geographical position favors investment in this field. Prospects in this sector require setting feed-in tariffsin the new RE law to create facilities not only in investment but also to subsidize the excess energy obtained.